Characterization of the transient fluorescence wave phenomenon that occurs during H2 production in Chlamydomonas reinhardtii - Krishna, Pilla Sankara (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.